The Role of Physical Activity, Enjoyment of Physical Activity, and School Performance in Learning Motivation among High School Students in Hungary - Tamás Berki; Zsófia Tarjányi (MDPI AG, 2022)
The goal of this study was to analyze the role of physical activity, enjoyment of physical activity, and school performance in the dimensions of learning motivation (Cognitive Domain, Affective Domain, Moral Domain, Adult Pressure). A total of 249 high school students were involved in this study, ranging in age from 14 to 19 years old. A self-administered questionnaire was filled out by the participants, including questions about sociodemographic background and school performance. The International Physical Activity Questionnaire was used to assess physical activity. Learning motivation was measured by the School Motivation Inventory. The Physical Activity Enjoyment Scale was used to determine the enjoyment of physical activity. Path analyses were chosen as a statistical method to understand the associations between the variables. Our findings reveal that learning motivation was associated with school performance and enjoyment of physical activity. Physical activity did not show any direct relationship with learning motivation, but it was positively associated with school performance and enjoyment of physical activity, hence showing an indirect relationship with learning motivation. Another important finding was the role of physical activity enjoyment. It has a preventive role concerning pressure from adults since such enjoyment strengthens the intrinsic motivation of students. We believe our findings highlight the benefits of physical activity and enjoyment of physical activity in learning environments.